Essential of Haematology - Kawthalkar, Shirish M. (New Dalhi : Jaypee Brothers,Medical Publishers Pvt. Ltd, 2013)
This work is a standard textbook of haemotology for medical students. It will provide students with an account of the essential features of clinical and laboratory haemotology, with selected reading lists and colour diagrams
Keywords: Hematologic Diseases; Blood -- Diseases